Enhancing motivation and learning achievement in IPAS through the environmental science, technology, and society approach in Elementary School - Palupi, Margiyanti; Utaminingsih, Retno; Murniningsih, Murniningsih (Bulletin of Educational Management and Innovation, 2025)
Background: This study addresses the low levels of student motivation and learning outcomes in the integrated science and social studies (IPAS) subject among fourth-grade students at SDN Mandungan. It aims to investigate the effectiveness of the Science, Environment, Technology, and Society (Salingtemas) approach in improving both motivation and academic performance. Method: The research employed a Classroom Action Research (CAR) design, implemented over two cycles involving planning, implementation, observation, and reflection. The participants were 30 fourth-grade students during the 2023/2024 academic year. Data were collected through observation sheets and tests, then analyzed using both quantitative and qualitative methods. Findings: The findings showed that the Salingtemas approach led to notable improvements: students’ motivation increased from 61.2% at the initial stage to 73.5% in Cycle I and 79% in Cycle II. Similarly, the average learning score rose from 73.33 to 83.3, exceeding the Minimum Mastery Criteria and achieving over 80% in class-wide mastery. These results indicate that the Salingtemas approach effectively enhances both motivation and learning outcomes in elementary IPAS education. This demonstrates that the Salingtemas approach significantly enhances both motivation and learning outcomes.